Changes in brain connectivity related to the treatment of depression measured through fMRI: a systematic review - Gudayol-Ferré, Esteve; Peró-Cebollero, Maribel; González-Garrido, Andrés A.; Guàrdia-Olmos, Joan (Frontiers in Human Neuroscience, 2015)
Depression is a mental illness that presents alterations of brain connectivity in the Default Mode Network, the Affective Network and other cortical-limbic networks, and the Cognitive Control Network (CCN) among others. In recent years the interest in the possible effect of the different antidepressant treatments on functional connectivity has increased substantially. The goal of this paper is to conduct a systematic review of the studies on the relationship between the treatment of depression and brain connectivity. Nineteen studies were found in the systematic review on this topic. In all of them, there was improvement of the clinical symptoms after antidepressant treatment. In 18 out of the 19 studies, clinical improvement was associated to changes in brain connectivity. It seems that both DMN and the connectivity between cortical and limbic structures consistently change after antidepressant treatment. However, the current evidence does not allow us to assure that the treatment of depression lead to changes in the CCN. In this regard, some papers report a positive correlation between changes in brain connectivity and improvement of depressive symptomatology, particularly when they measure cortical-limbic connectivity, whereas the changes in DMN do not significantly correlate with clinical improvement. Finally, some papers suggest that changes in connectivity after antidepressant treatment might be partly related to the mechanisms of action of the treatment administered. This effect has been observed in two studies with stimulation treatment (one with rTMS and one with ECT), and in two papers that administered three different pharmacological treatments. us to make a series of recommendations that, on the one hand, might guide future researchers exploring the effect of anti-depression treatments on brain connectivity.